2018
DOI: 10.18632/aging.101507
|View full text |Cite
|
Sign up to set email alerts
|

Cumulus cell-released tumor necrosis factor (TNF)-α promotes post-ovulatory aging of mouse oocytes

Abstract: Although previous studies indicated that cumulus cells (CCs) accelerate oocyte aging by releasing soluble factors, the factors have yet to be characterized. While demonstrating that CCs promoted oocyte aging by releasing soluble Fas ligand (sFasL), our recent study suggested that CCs might secrete other factors to mediate oocyte aging as well. This study tested whether CCs accelerate oocyte aging by secreting tumor necrosis factor (TNF)-α. The results showed that mouse CCs undergoing apoptosis released soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…In this study, transcriptome analysis revealed that only four differentially expressed genes were upregulated in the cumulus cells and only four were downregulated in oocytes, indicating that LPA had varying effects on the gene expression of cumulus cells and oocytes. KEGG pathway enrichment analysis revealed upregulated and downregulated genes in the cumulus cells that enrich the TNF signaling pathway, and the cumulus cells can release soluble TNF-α to promote oocyte aging (32). In our study, the upregulated genes in the cumulus cells enriched the insulin secretion pathway.…”
Section: Discussionsupporting
confidence: 51%
“…In this study, transcriptome analysis revealed that only four differentially expressed genes were upregulated in the cumulus cells and only four were downregulated in oocytes, indicating that LPA had varying effects on the gene expression of cumulus cells and oocytes. KEGG pathway enrichment analysis revealed upregulated and downregulated genes in the cumulus cells that enrich the TNF signaling pathway, and the cumulus cells can release soluble TNF-α to promote oocyte aging (32). In our study, the upregulated genes in the cumulus cells enriched the insulin secretion pathway.…”
Section: Discussionsupporting
confidence: 51%
“…KEGG pathway enrichment analysis revealed upregulated and downregulated genes in the CCs that enrich the TNF signaling pathway, and the CCs can release soluble TNF-α to promote oocyte aging [24]. In our study, the upregulated genes in the CCs enriched the insulin secretion pathway.…”
Section: Discussionsupporting
confidence: 51%
“…Li et al demonstrated that oxidative stress induced bovine GC apoptosis by increasing the expression of cleaved caspase-3 and the Bax/Bcl-2 ratio as well as decreasing the expression of antioxidant enzymes (SOD2, glutathione peroxidase (GSH-Px)) ( Wang Y et al, 2019 ). In addition, excessive ROS in oocytes and GCs can induce the release of TNFα ( Kong et al, 2018 ; Miao et al, 2018 ). TNF-α binds to its death receptors (such as Fas and TNFR) and then activates the death receptor (extrinsic) pathway of apoptosis through Fas-associated death domain-dependent activation of caspase-8 ( Morgan et al, 2008 ; Guicciardi and Gores, 2009 ; Redza-Dutordoir and Averill-Bates, 2016 ).…”
Section: Effects Of Oxidative Stress On Apoptosis In the Ovariesmentioning
confidence: 99%